CLAME : a new alignment-based binning algorithm allows the genomic description of a novel Xanthomonadaceae from the Colombian Andes (2018)
ABSTRACT : Background: Hot spring bacteria have unique biological adaptations to survive the extreme conditions of these environments; these bacteria produce thermostable enzymes that can be used in biotechnological and industrial applications. However, sequencing these bacteria is complex, since it is not possible to culture them. As an alternative, genome shotgun sequencing of whole microbial communities can be used. The problem is that the classification of sequences within a metagenomic dataset is very challenging particularly when they include unknown microorganisms since they lack genomic reference. We failed to recover a bacterium genome from a hot spring metagenome using the available software tools, so we develop a new tool that allowed us to recover most of this genome. Results: We present a proteobacteria draft genome reconstructed from a Colombian’s Andes hot spring metagenome. The genome seems to be from a new lineage within the family Rhodanobacteraceae of the class Gammaproteobacteria, closely related to the genus Dokdonella. We were able to generate this genome thanks to CLAME. CLAME, from Spanish “CLAsificador MEtagenomico”, is a tool to group reads in bins. We show that most reads from each bin belong to a single chromosome. CLAME is very effective recovering most of the reads belonging to the predominant species within a metagenome. Conclusions: We developed a tool that can be used to extract genomes (or parts of them) from a complex metagenome.